2021
DOI: 10.1007/s11119-021-09854-3
|View full text |Cite
|
Sign up to set email alerts
|

German farmers’ intention to use autonomous field robots: a PLS-analysis

Abstract: Autonomous field robots are a promising technology for solving several problems in agriculture, as they are electrical driven, can control weeds single-plant based mechanically or with microdoses of pesticides and exert less ground pressure on the field. Whether such robots will be applied on a large scale in German agriculture depends on various parameters. Therefore, the factors influencing the behavioural intention of farmers with respect to their future adoption of autonomous field robots were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 74 publications
1
5
0
Order By: Relevance
“…Furthermore, von Veltheim and Heise (2021) concluded that the surveyed German farmers tended to have a neutral to positive view on adopting field crop robots, aligned with von Veltheim et al. (2021), who also found that the surveyed German farmers were positive about introducing autonomous field robots on their farms.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…Furthermore, von Veltheim and Heise (2021) concluded that the surveyed German farmers tended to have a neutral to positive view on adopting field crop robots, aligned with von Veltheim et al. (2021), who also found that the surveyed German farmers were positive about introducing autonomous field robots on their farms.…”
Section: Resultsmentioning
confidence: 58%
“…Additionally, von Veltheim et al. (2021) showed a moderating effect of age on the effect of variables on the intention to adopt. Furthermore, male farmers were more likely to have a higher intention to adopt or adoption rate of robotics and UAVs than female farmers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These approaches lack the principles of substantive inclusion identified above (Rose and Bhattacharya, 2023). Examples of participation and inclusion in the technical dimensions of agricultural robotic development have thus far employed a range of tools, including the use of augmented reality (Huuskonen & Oksanen, 2019), on-farm trials (Adamides et al, 2017) and simulation events (see Riek, 2012 for methods), farmer surveys (Rose and Bhattacharya, 2023;Tamirat et al, 2023;von Veltheim and Heise, 2021;von Veltheim et al, 2022), public surveys (Pfeiffer et al, 2021;Spykman et al, 2022) and farmer interviews (Redhead et al, 2015). A recent study in four European countries by Tamirat et al (2023) went further than including only farmers, and instead interviewed robotic companies, academics, project managers, public authorities, and environmental conservation societies.…”
Section: Inclusion For Agricultural Robotics To Datementioning
confidence: 99%
“…They also predicted that farms with larger fields would adopt field crop robots sooner than farms with small fields, irrespective of total acreage, due to logistic costs. Rübcke von Veltheim et al ( 2022 ) further investigated the behavioural intention of German farmers with respect to their future adoption of autonomous field robots. It is found that farmers’ expected performance and trust in technology had a significant positive impact on their intention to adopt autonomous field robots.…”
Section: Literature Reviewmentioning
confidence: 99%